Thermal performance and heat transfer characteristics analyses of oxy-biogas combustion in a swirl stabilized boiler under various oxidizing environments. (15th December 2022) - Mohammadpour, Mohammadreza; Ashjaee, Mehdi; Houshfar, Ehsan
Abstract: The present study deals with the numerical simulation of biogas diffusion flame in swirl stabilized boiler under different oxy-combustion conditions. The current study aims to investigate the impacts of O2 /CO2 and O2 /H2 O oxidizer mixtures on the thermal and combustion characteristics of biogas flame in the boiler. Accordingly, the combustion simulation process is performed by the k-ω SST turbulence, DO radiation, and Flamelet Generated Manifold (FGM) combustion models. Results showed that by the increasing swirl angle, heat flux uniformity factor (UF) enhances by 26.8% and 129.9% for O2 /CO2 and O2 /H2 O combustion modes, respectively. Also, by raising O2 %, the flame peak temperature increases from 1832 K to 2171 K in O2 /CO2 mode and from 2053 K to 2283 K in O2 /H2 O case. It was observed that the maximum of UF on the boiler wall could be achieved to be 0.81 at SA 60° in oxy-steam mode. Moreover, the UF value significantly increases by 39.42% on the boiler wall by transitioning from O2 /CO2 to O2 /H2 O combustion mode at higher O2 content. Finally, results imply that there is no need to increase O2 content beyond 50% to reach higher heat transfer rate in O2 /H2 O mode because this would result in additional costs. Highlights: CFD simulation of oxy-biogas combustion in swirl stabilized boiler has been studied. By transition from O2 /CO2 to O2 /H2 O, the heat flux uniformity significantly boosts. Highest value of Uf can be achieved by SA60° in O2 /H2 O combustion mode. Raising O2 % has almost no effect on heat flux uniformity in both combustion modes. The highest total heat transfer rate can be found in SA30° for O2 /CO2 mode.